Breeding Habitat and Landscape Correlates of Frog Diversity and Abundance in a Tropical Agricultural Landscape - da Silva, Fernando Rodrigues; Gibbs, James P.; Rossa-Feres, Denise de Cerqueira [UNESP] (Springer, 2011)
The biodiversity values of temporary pools in tropical ecosystems are poorly understood. Such wetlands are often threatened by agriculture. Constructed pools provide a means to mitigate for loss of natural pools but design features associated with restoration successful are not known. In this paper, we evaluated the effects of environmental variables at local (breeding pools) and regional spatial scales (landscape configuration) on species richness and abundance of anurans in heavily altered landscapes of southeastern Brazil. Frog and toad communities of 18 constructed temporary breeding pools were sampled every 2 weeks from October 2008 to March 2009. Two variables-hydroperiod and percentage of vegetation in the interior of the pools-explained 62% of species richness variation. Three other variables-pool area, distance of pools to forest fragments, and distance of pools to road-explained between 22 and 46% of the variation in frog and toad abundance. Our results indicate that local- and regional-scale variables, and their interaction, are important drivers of the structure of frog and toad communities in these agricultural landscapes. To facilitate amphibian conservation we suggest that cattle ranchers create and maintain heavily vegetated temporary pools near protected forest reserves as both a water source for livestock and breeding habitat for amphibians.
Keywords: Amphibians; Brazil, Conservation; Hierarchical partitioning; Scale; Temporary pools